High test positivity and low positive predictive value for colorectal cancer of continued faecal occult blood test screening after negative colonoscopy. (June 2018) - Brown, Jeremy P; Wooldrage, Kate; Wright, Suzanne; Nickerson, Claire; Cross, Amanda J; Atkin, Wendy S
Objectives: The English Bowel Cancer Screening Programme offers biennial guaiac faecal occult blood test (gFOBT) screening to 60–74-year-olds. Participants with positive results are referred for follow-up, but many do not have significant findings. If they remain age eligible, these individuals are reinvited for gFOBT screening. We evaluated the performance of repeat screening in this group. Methods: We analysed data on programme participants reinvited to gFOBT screening after either previous negative gFOBT ( n = 327, 542), or positive gFOBT followed by a diagnostic investigation negative for colorectal cancer (CRC) or adenomas requiring surveillance ( n = 42, 280). Outcomes calculated were uptake, test positivity, yield of CRC, and positive predictive value (PPV) of gFOBT for CRC. Results: For participants with a previous negative gFOBT, uptake in the subsequent screening round was 87.5%, positivity was 1.3%, yield of CRC was 0.112% of those adequately screened, and the PPV of gFOBT for CRC was 9.1%. After a positive gFOBT and a negative diagnostic investigation, uptake in the repeat screening round was 82.6%, positivity was 11.3%, CRC yield was 0.172% of participants adequately screened, and the PPV of gFOBT for CRC was 1.7%. Conclusion: With high positivity and low PPV for CRC, the suitability of routine repeat gFOBT screening in two years among individuals with a previous positive test and a negative diagnostic examination needs to be carefully considered.